MiR‐132 suppresses transcription of ribosomal proteins to promote protective Th1 immunity. (4th March 2019) - Hewitson, James P; Shah, Kunal M; Brown, Najmeeyah; Grevitt, Paul; Hain, Sofia; Newling, Katherine; Sharp, Tyson V; Kaye, Paul M; Lagos, Dimitris
Abstract: Determining the mechanisms that distinguish protective immunity from pathological chronic inflammation remains a fundamental challenge. miR‐132 has been shown to play largely immunoregulatory roles in immunity; however, its role in CD4 + T cell function is poorly understood. Here, we show that CD4 + T cells express high levels of miR‐132 and that T cell activation leads to miR‐132 up‐regulation. The transcriptomic hallmark of splenic CD4 + T cells lacking the miR‐132/212 cluster during chronic infection is an increase in mRNA levels of ribosomal protein (RP) genes. BTAF1, a co‐factor of B‐TFIID and novel miR‐132/212‐3p target, and p300 contribute towards miR‐132/212‐mediated regulation of RP transcription. Following infection with Leishmania donovani, miR‐132 −/− CD4 + T cells display enhanced expression of IL‐10 and decreased IFNγ. This is associated with reduced hepatosplenomegaly and enhanced pathogen load. The enhanced IL‐10 expression in miR‐132 −/− Th1 cells is recapitulated in vitro following treatment with phenylephrine, a drug reported to promote ribosome synthesis. Our results uncover that miR‐132/212‐mediated regulation of RP expression is critical for optimal CD4 + T cell activation and protective immunity against pathogens. Synopsis: The miR‐132/212 cluster plays important roles in acute inflammation and infection. This study shows that during pathogen‐induced chronic inflammation miR‐132‐mediated regulation of ribosomal protein expression is critical for CD4 + T cell activation and protective immunity. Up‐regulation of the miR‐132/212 cluster suppresses ribosomal protein (RP) expression in Th1 cells. The miR‐132/212 cluster targets BTAF1 and p300, which control RP gene transcription. RP levels in Leishmania ‐infected miR‐132/212 −/− mice correlate with increased IL‐10 expression in Th1 cells. Infected miR‐132/212 −/− mice show reduced hepatosplenomegaly and increased parasite burdens. Abstract : The miR‐132/212 cluster plays important roles in acute inflammation and infection. This study shows that during pathogen‐induced chronic inflammation miR‐132‐mediated regulation of ribosomal protein expression is critical for CD4 + T cell activation and protective immunity.